Good Friday Mass - Mumbai Archive Project Team (Jio Institute, 2024)
Good Friday Mass includes Scripture readings, with a focus on Jesus’ suffering and crucifixion. The narration typically commences with two individuals portraying Jesus’ followers, engaging the audience in a discussion about the events leading up to the crucifixion.